KARAKTER BARKODING DNA SIANOBAKTER ASAL AIR RAWA DAN KOLAM BUDIDAYA PATIN DI OGAN ILIR SUMATERA SELATAN - Marini Wijayanti; Dade Jubaedah; Tanbiyaskur Tanbiyaskur; Novi Wulandari Mustika; Nuni Gofar (Jurnal Akuakultur Rawa Indonesia, 2022)
Pangasius catfish rearing ponds and swamp waters are types of stagnant waters (lentic) that are commonly found in the South Sumatra region. Cyanobacter is a group of phytoplankton that plays an important role in the management of aquatic area, but it is not widely known which species is the most dominant in swamp waters. This study aims to determine the types of cyanobacter that are abundant in the swamps and Pangasius catfish cultivation ponds in Ogan Olir, South Sumatra. This research has been carried out by cyanobacter isolation from the swamp water and the pond, isolate liquid cultivation, DNA isolation, 16S rRNA gene amplification and DNA amplicon sequencing. The sequencing results were analyzed using BLAST (Basic local alignment search tool-nucleotide) and MEGA 6 with the help of NCBI gene bank data to obtain a phylogenetic tree for predicting the identity of the cyanobacter isolates. Based on the morphological characters, it is suspected that the pond isolates are similar to Synechoccocus and swamp isolates similar to Microcystis genera. The amplification of cyanobacter DNA using the PCR method with the universal 16S rRNA 63F (Forward) and 1387 R (Reverse) resulted 1302-1307 base pairs. Analysis using BLAST showed that the cyanobacter isolates from ponds have 91% similar to Uncultured Synechoccocus sp. from Australia, while the swamp isolates have 86% similar to Microcystis sp. from China. Key words : Cyanobacteria, Microcystis, PCR, Phylogenetic, Synechococcus